Motivasi Pembelajaran Piano pada Anak Autis di Studio Musik Markas Kota Prabumulih - Aurora, Galuh Liony Putri; Heryanto, A; Hidayatullah, Fadhilah (Institut Teknologi Pendidikan Indonesia, 2022)
The formulation of the problem in this study is: How is the learning process between teachers and children with autism in piano learning at the Prabumulih City Headquarters Music Studio? The purpose of this study was to determine the process of learning piano music for autistic children at the Prabumulih City Headquarters Music Studio. The method used in this research is a qualitative descriptive method, which is a research method based on nonnumeric data, collecting and analyzing narrative data. The sample in this study amounted to 1 student. The techniques used in collecting research data were carried out using: observation, interviews, and documentation. The data obtained from the interviews were analyzed using qualitative data analysis. Based on the results of data analysis, it is known that: 1) Learning piano musical instruments for autistic children at the Prabumulih City Headquarters Music Studio is quite good and has been running according to non-formal school standards or course venues in general 2) At the implementation stage also students who are autistic children have quite active because students are very enthusiastic and excited in learning to play the piano musical instrument.